STUDI TENTANG GETARAN DALAM HUMAN DISPLAY INTERFACE DAN PENGARUHNYA TERHADAP KELUHAN SUBYEKTIF OPERATOR DI PT ? EJ ? DENPASAR SELATAN. - Sucipta, Nyoman (Agrotekno, 2012)
The aim of this research is to study the effect of vibration in human display interface on operator subjective complaint at PT ?EJ? in South Denpasar. Methods used in this research are observations and measurements on the operators and environmental conditions. Variables involved in this research are namely: the operators? age, weight and height, dry and wet bulb temperatures, humidity and noise level. The results showed that the average age, weight and height of the operators were 26,71 (? 7,13) years, 58 ,4 ( ? 1,1) kg, and 164, 14 (?3,43) cms respectively. The wet and dry bulb temperature were 26?C and 30?C. The humidity was 86 % and the noise level was > 80 dB. The operator complaints were: severe low backpain, pressure on breathing, feeling thirsty, tremor, feeling unhealthy and feeling stiff at the eyelid. The effect of vibration on human display interface depended on the operator position at work. The operators who were sit while working, vibration occurred at the axis of the seat. But, the workers who were standing while working, vibration occurred at 8-10 Hz resonance.
Keywords: Getaran, human display interface, keluhan subyektif